The long arm of childhood socioeconomic deprivation on mid‐ to later‐life cognitive trajectories: A cross‐cohort analysis. Issue 1 (1st June 2022) - Tsang, Ruby S. M.; Gallacher, John E.; Bauermeister, Sarah
Abstract: Introduction: Earlier studies of the effects of childhood socioeconomic status (SES) on later‐life cognitive function consistently report a social gradient in later‐life cognitive function. Evidence for their effects on cognitive decline is, however, less clear. Methods: The sample consists of 5324 participants in the Whitehall II study, 8572 in the Health and Retirement Study (HRS), and 1413 in the Kame Project, who completed self‐report questionnaires on their early life experiences and underwent repeated cognitive assessments. We characterized cognitive trajectories using latent class mixed models, and explored associations between childhood SES and latent class membership using logistic regressions. Results: We identified distinct trajectories classes for all cognitive measures examined. Childhood socioeconomic deprivation was associated with an increased likelihood of being in a lower trajectory class. Discussion: Our findings support the notions that cognitive aging is a heterogeneous process and early life circumstances may have lasting effects on cognition across the life‐course.